Simulation of a TRIGA Reactor Core Blockage Using RELAP5 Code - Patrícia A. L. Reis; Antonella L. Costa; Claubia Pereira; Maria Auxiliadora F. Veloso; Amir Z. Mesquita (Science and Technology of Nuclear Installations)
Cases of core coolant flow blockage transient have been simulated and analysed for the TRIGA IPR-R1 research reactor using the RELAP5-MOD3.3 code. The transients are related to partial and to total obstruction of the core coolant channels. The reactor behaviour after the loss of flow was analysed as well as the changes in the coolant and fuel temperatures. The behaviour of the thermal hydraulic parameters from the transient simulations was analysed. For a partial blockage, it was observed that the reactor reaches a new steady state operation with new values for the thermal hydraulic parameters. The total core blockage brings the reactor to an abnormal operation causing increase in core temperature.